Association of Traffic-Related Air Pollution with DNA Damage and Some Other Biological Parameters among Minibuses Drivers in Baghdad City - Khalid, Fatima K.; Rabee, Adel M. (Iraqi Journal of Science, 2025)
Fifty blood samples were collected from minibus drivers aged 18-50 years a minimum driving experience of 2 years. The control group involved fifty age matched men who lived in other areas in Baghdad. The results illustrated that the level of both superoxide dismutase and glutathione enzymes were significantly decreased in the drivers group (9.87 ±0.32 µg/ml and 17.73 ±0.41 mg/ml respectively) as compared to the control group (38.00 ±1.78 µg/ml and64.92 ±2.04 mg/ml respectively). The level of catalase enzyme showed a highly significant increase in the drivers group (327.76 ±11.77 µg/ml) as compared to the control group (93.98 ±2.67 µg/ml). The results also showed a highly significant increase in the level of serum tumor necrosis factor alpha in the drivers group (332.17 ±11.84 pg/ml) as compared to the control (52.75 ±2.72 pg/ml). DNA damage showed a significant increase in the drivers group  (4.51 ±0.15 pg/ml) as compared to the control group(1.20 ±0.04 pg/ml).